The inner structure of the Jacobi-Laurent matrix related to the strong Hamburger moment problem - Dudkin, M. E. (Methods of Functional Analysis and Topology, 2013)
The form of the Jacobi type matrix related to the strong Hamburger moment problem is known N5,BD, i.e., there are known the zero elements of corresponding matrix. We describe the relations between of non-zero elements of such matrices, i.e., we describe ’’the inner structure’’ of the Jacobi-Laurent matrices related to the strong Hamburger moment problem.